The design of residential living spaces, and the influence of user needs, activities, and preferences - Salma Magdy Khalil Abdelfattah; Hisham S. Gabr (Cairo : Salma Magdy Khalil Abdelfattah, 2021)
Home and living spaces are worth studying because they are consequential real-world settings in which basic psychological processes are regularly played out.This study illustrates the potential insights within the living spaces that have some psychological ambiences that users desire (e.g., comfort, togetherness, restoration, intimacy, productivity, and so on). Users{u2019}emotions effect positively on the space mood. Most users furnish their living spaces without being aware enough of the interior design principles and its effect on their energy and psychology. In this study, the effect of three elements (furniture arrangement, color scheme, and lighting) were studied on the users through an interview questionnaire to illustrate their mood, behavior and productivity.The existing condition for ten random samples were included in this study, spaces were modified according to the theoretical design principals which contribute in living a better healthy life
Thesis (M.Sc.) - Cairo University - Faculty of Engineering - Department of Architectural Engineering
Issued also as CD
Keywords: Furniture; Living room; Psychology